Trabalho e cultura organizacional no discurso da mídia: uma análise da revista Você S/A - Britto, Denise Fernandes (2014)
The culture of work, comprising the values, ideas and shared behaviors between individuals in organizations, has been modified from the restructuring process. The objective of this research is to identify how the organizational discourse constructed by the media reinforces ideologically such transformations, generating a representation of the desired profile of the contemporary worker. For this, we analyze news from the magazine Você S/A on its Career section, based on categories of Discourse Analysis and sociological theory about the world of work. The topics more focused by the magazine were analyzed in relation to discursive aspects of intertextuality and interdiscursivity in written texts and images of the articles. Thus, it was possible to realize that organizational culture in media discourse follows the business management perspective, regulatory and uncritical. The ideological process hide the mechanisms of pressure and overload work by enhancing the desired values of the new worker's profile, based on autonomy, skills, flexibility and innovation. Figures such as coach, consultant, leader, entrepreneur and professionals related to human resources are central to the consolidation of work and organizational culture. In addition, there is a convergence between journalistic, business and educational discourses, focused on the executive worker training that compounds the public of Você S/A. The reports prescribe "recipes" that are assertive when discuss the employee's responsibilities, while the benefits are only in the bound of possibilities.